Contribution to the knowledge of species of the genus Anthrenus, subgenus Florilinus from Bulgaria (Coleoptera: Dermestidae: Anthrenini) - Háva, Jiři (Acta entomologica slovenica (Ljubljana), 2006)
Anthrenus (Florilinus) kourili sp. n. is described, illustrated and compared with all known species of the subgenus Florilinus Mulsant et Rey, 1868 occurring in Bulgaria. The Anthrenus (F.) olgae Kalík, 1946 is recorded from Bulgaria for the first time.
Keywords: Bolgarija; Bulgaria; entomologija; favna; hrošči